2003
DOI: 10.1021/ja036111q
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Dendritic Gels:  Easily Tunable Materials

Abstract: This paper reports the tunability of a two-component gel system based on dendritic l-lysine with a focal point carboxylic acid group and aliphatic diamines. The microscopic structure and macroscopic properties of the gel can be modulated by changing the concentration of the components, altering their molecular structures, or tuning their relative molar ratio. In the latter case, there is a complete change in the morphology of the gel that has a direct impact on its macroscopic properties, specifically its gel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(98 citation statements)
references
References 6 publications
2
96
0
Order By: Relevance
“…The critical gelation concentrations (C gel ) and critical gel-sol transition temperatures (T gel ) were determined through tube inversion technology. 36 As shown in Table 1, the C gel of the synthesized BDB triblock copolymers varied from 3.50 wt% to 0.30 wt% and the T gel varied from 41 to 45 C. And the value of C gel decreased with the increase of PBLG length, while the T gel increased as the PBLG length increased. Thus, the degree of polymerization of the PBLG block had an important effect on the gelation of PBLG-b-PDMS-b-PBLG triblock copolymers since the stacking between the PBLG helices in combination with the p-p interaction were the main driving force of the self-assembly.…”
Section: The Gelation Behaviors Of Bdb Tribcps With the Incorporationmentioning
confidence: 90%
See 2 more Smart Citations
“…The critical gelation concentrations (C gel ) and critical gel-sol transition temperatures (T gel ) were determined through tube inversion technology. 36 As shown in Table 1, the C gel of the synthesized BDB triblock copolymers varied from 3.50 wt% to 0.30 wt% and the T gel varied from 41 to 45 C. And the value of C gel decreased with the increase of PBLG length, while the T gel increased as the PBLG length increased. Thus, the degree of polymerization of the PBLG block had an important effect on the gelation of PBLG-b-PDMS-b-PBLG triblock copolymers since the stacking between the PBLG helices in combination with the p-p interaction were the main driving force of the self-assembly.…”
Section: The Gelation Behaviors Of Bdb Tribcps With the Incorporationmentioning
confidence: 90%
“…Gelation concentration was determined by preparing a series of different concentrated solutions and the gelation was monitored by tube inversion technique. 36,37 And the sol-gel transition temperature was monitored by tube inversion technique during heating process of the gel.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Increasing the amount of diamine relative to the dendritic branch changed the propensity of this system to induce macroscopic gelation, and ultimately gave rise to a completely new morphology in which micrometer sized platelets were observed ( Figure 2).…”
Section: Two-component Organogelatorsmentioning
confidence: 99%
“…In a key study, Smith, Hirst and co-workers reported that the morphology of the nanoscale aggregates formed could be directly controlled using the ratio of dendrimer:diamine ( Figure 54) [138]. A 2:1 ratio gave rise to the expected fibrillar aggregates.…”
Section: Assembly Of One-dimensional Architectures Using Multiple Recmentioning
confidence: 99%